2023
DOI: 10.1002/vnl.22053
|View full text |Cite
|
Sign up to set email alerts
|

Rhodanine‐chitosan hydrogel as a novel antioxidant for acrylonitrile‐butadiene rubber composites

T. A. Zidan

Abstract: Rhodanine‐chitosan (RC) hydrogel is examined as a novel antioxidant for acrylonitrile‐butadiene rubber (NBR) composites. RC is added to NBR with different proportions (1, 2 phr) and compared to the commercial 2,2,4‐trimethyl‐1,2‐dihydroquinoline polymer (TMQ) antioxidant. Physico‐mechanical properties including tensile strength, elongation, and modulus are also studied. It is found that NBR composite containing 2 phr of RC has the most favorable mechanical properties. The formed composites were subjected to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Swelling of the prepared EPDM composites before and after aging was done in toluene for 24 h according to ASTM D573-2007. Molecular weight between two crosslinks (Mc) was determined using swelling data by applying Flory-Rehner equation according to the following relation 19 :…”
Section: Swelling Properties and Crosslink Density Of The Prepared Ep...mentioning
confidence: 99%
“…Swelling of the prepared EPDM composites before and after aging was done in toluene for 24 h according to ASTM D573-2007. Molecular weight between two crosslinks (Mc) was determined using swelling data by applying Flory-Rehner equation according to the following relation 19 :…”
Section: Swelling Properties and Crosslink Density Of The Prepared Ep...mentioning
confidence: 99%
“…For example, Xie et al 22 synthesized a macromolecular antioxidant CS‐UC‐GA containing amide, carbon–carbon double bond, and phenolic hydroxyl group by grafting 10‐undecylenoyl chloride (UC) and gallic acid (GA) into chitosan (CS), and found that CS‐UC‐GA with superior extraction resistance could endow styrene‐butadiene rubber (SBR)/SiO 2 composites with better thermo‐oxidative aging resistance. The utilization of CS as a matrix and its chemical modification as a macromolecular antioxidant can broaden the application of CS and promote the development of the rubber industry, as well as help to make full use of resources and protect the environment 23 …”
Section: Introductionmentioning
confidence: 99%